THE INFLUENCE OF CUSTOMER AWARENESS AND UTILIZATION OF GREEN BANKING SERVICES ON E-BANKING ADOPTION - Sowmya M; Prabakaran G (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The adoption of e-banking has become increasingly important in today's digital era, and green banking plays a significant role in shaping this adoption. Green banking encompasses environmentally sustainable practices within the banking sector, promoting eco-friendly initiatives and reducing carbon footprints. Recognizing the importance of green banking for the adoption of e-banking is crucial in understanding the larger impact of these practices on both customers and the banking industry. The study aims to determine the major drivers of e-banking adoption by analyzing factors such as customer awareness, utilization, perceived quality, efficiency, and cost of green banking services. Surveys were conducted to gain insights into customers' perceptions and opinions regarding green banking services in e-banking operations. The research design employed was descriptive, utilizing a purposive sampling method with a sample size of 201 customers. The primary data was collected through structured questionnaires, while secondary data was gathered from magazines and websites. The study recommends that the banking sector should educate and motivate customers about the benefits of green banking, including time-saving, trust-building, convenience, timely account statements, and enhanced security. Statistical techniques such as chi-square tests, regression analysis, correlation analysis (Karl Pearson's), and one-way ANOVA were employed. This research provides valuable insights for the banking sector to understand customers' effective utilization of green banking services and their interest in e-banking adoption. Furthermore, the research endeavors to highlight how sustainable initiatives can have a transformative impact on the future of the banking industry.